The Effect of Ice Massage and Passive Stretching on the DOMS of the Gastrocnemius Muscle - Hadad Akbar, Muhammad Thoriq; Doewes, Muchsin; Syaifullah, Rony (Quality in Sport, 2023)
Delayed onset muscle soreness (DOMS) is a disorder in the form of muscle soreness that occurs as a result of unusual exercise caused by an inflammatory response. DOMS is often experienced by all individuals who do too much physical activity after a long period of inactivity. DOMS can be experienced by anyone who does non-routine sports activities. This study aims to find out about the effect of ice massage and passive stretching on the DOMS of the gatrocnemius muscle. The sample used in this study was 100, which consisted of UTP Surakarta students obtained by purposive random sampling technique. Statistical analysis was carried out on the initial results of DOMS after training and the final results of DOMS after being given ice massage and passive stretching treatment to male and female students. The results of statistical analysis were carried out using the SPSS version 25 program. There is a significant difference in the effect of ice massage and passive stretching on decreasing DOMS in the Gastrocnemius muscles. This is evidenced by the Significance value of 0.036 < 0.05 (p < 0.05). So it can be concluded that giving ice massage has a decrease in DOMS which is different from giving passive stretching which can be accepted.